The psychosocial growth of preschool-age children from broken home families - Indrawati, Triana; Dewi, Lutviana (Universitas Islam Negeri Raden Intan Lampung, 2022)
This study is driven by a broken home family, which results in children not receiving unconditional love from their parents, particularly a father role. The research aims to determine the subject's psychological development in a broken home family, as well as the impact created by the research subject. Researchers employed a qualitative research approach with a case study research design. Interviews and observations made during the investigation were used to collect data. Whereas the data sources used were from the field during the research with supporting informants, as well as earlier research results, journals, and books that helped and were consistent with the studies presented. The difference between this study and previous research is that previous research discussed whether or not there is a significant relationship between family relationships and psychoanalytic stimulus. In contrast, this study discusses the psychosocial impacts and determines psychosocial development in children from broken-home families. According to the study's findings, children from broken homes have beneficial consequences, such as having an independent attitude, and negative impacts, such as a loss of affection from parents, difficulties socializing, and a lack of confidence. According to the findings of the research, broken home families have a significant impact on the psychosocial development of early infancy.